Regioselective alkylation of a versatile indazole: Electrophile scope and mechanistic insights from density functional theory calculations - Lu, Pengcheng; Juarez, Luis; Wiget, Paul A.; Zhang, Weihe; Raman, Krishnan; Kotian, Pravin L. (Beilstein Journal of Organic Chemistry, 2024)
Herein, we report a pair of regioselective N1- and N2-alkylations of a versatile indazole, methyl 5-bromo-1H-indazole-3-carboxylate (6) and the use of density functional theory (DFT) to evaluate their mechanisms. Over thirty N1- and N2-alkylated products were isolated in over 90% yield regardless of the conditions. DFT calculations suggest a chelation mechanism produces the N1-substituted products when cesium is present and other non-covalent interactions (NCIs) drive the N2-product formation. Methyl 1H-indazole-7-carboxylate (18) and 1H-indazole-3-carbonitrile (21) were also subjected to the reaction conditions and their mechanisms were evaluated. The N1- and N2-partial charges and Fukui indices were calculated for compounds 6, 18, and 21 via natural bond orbital (NBO) analyses which further support the suggested reaction pathways.
Keywords: DFT; indazole; indazole substitution; mechanism; N1-substituted indazole; N2-substituted indazole; regioselectivity